The ABC of the foreign exchanges - Crump, Norman; Clare, George (London: Macmillan, 1956)
This book gives account of the startling changes in the international economy. It gives account of the foreign exchange system up to 1939. The war-time regulations are outlined, the nature of the post war financial institution explained, and also the main lines of intra-European economic relations.
"The first edition ... was written by Mr. George Clare and published in 1892."
usc 07/06/2018
Loans
Keywords: Foreign exchange